Patenting life? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Plant variety rights exist to provide legal protection for improved plant strains. In developing countries, requests for such rights are often registered by foreign producers in the country, usually large agro-industrial companies. The chart here...